Analysing the role of information exchange for demand forecasting in collaborative supply chains - Ramanathan, Usha (2010)
It is now widely recognized that supply chains, not individual organisations, are responsible for the success or failure of businesses. This has necessitated close coordination among supply chain partners. In the past few decades, in an attempt to improve the overall efficiency of the supply chain, many companies have engaged in collaboration with other supply chain members. Consequently, several supply chain management initiatives such as Vendor Managed Inventory, Efficient Consumer Response, Continuous Replenishment and Accurate Response have been proposed in the literature to improve the flow of materials as well as information among supply chain partners. In this line, Collaborative Planning Forecasting and Replenishment (CPFR) is a relatively new initiative that combines the intelligence of multiple trading partners in planning and fulfilment of customer demand by linking sales and marketing best practices. The role of CPFR has been widely studied in the US retail industry, but it has not been researched much in the UK and also in Asian countries. Hence, this research focuses on the adoption of CPFR in the UK and India.